3GPa ultrahigh-strength corrosion-resistant rigging steel and preparation method thereof

By adding Al and Mo elements to T8 carbon steel, ultrafine crystal 0.8C3Al0.7Mo rigging steel is designed, and hot rolling and cold drawing processes are adopted to solve the problem of insufficient strength and corrosion resistance of existing rigging steels, and the improvement of 3GPa ultra-high strength and excellent corrosion resistance is achieved, and it is suitable for many important fields.

CN119776725AActive Publication Date: 2025-04-08INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411943315.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing rigging steels have shortcomings in strength and corrosion resistance, especially the corrosion resistance of cold-drawn pearlite steel wires is poor, which leads to prone to rust during service and increases the preparation cost.

Method used

By adding Al and Mo elements to traditional T8 carbon steel, ultrafine crystal 0.8C3Al 0.7Mo rigging steel was designed, and rigging steel with 3GPa ultra-high strength and excellent corrosion resistance was prepared using vacuum induction furnace smelting, hot rolling and cold drawing processes.

Benefits of technology

The high strength and corrosion resistance of rigging steel have been improved, with a yield strength of 2150~3050MPa, a tensile strength of 2550~3450MPa, an elongation of 3~10%, and a self-corrosion current in 3.5% NaCl aqueous solution is 0.2~1μA/cm2, which is suitable for marine cables, large-span bridge cables and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776725A_ABST
    Figure CN119776725A_ABST
Patent Text Reader

Abstract

The invention discloses 3GPa ultrahigh-strength corrosion-resistant rigging steel, which comprises the following chemical components in percentage by weight: 0.6-1.0 percent of C, 0.6-1.0 percent of C, 0.2-1.0 percent of Cr, 0.2-1.0 percent of Mo, 0.2-1.0 percent of Mo 2.2 to 3.8 parts of Al; 0.3 to 1.1 parts of Mo; and the balance of Fe. The preparation method of the 3GPa ultrahigh-strength corrosion-resistant rigging steel meets the following requirements that the initial structure of a hot-rolled blank is a full-martensite structure, multi-pass hot rolling is conducted on the structure in an (alpha + gamma) two-phase region at the temperature of 800-880 DEG C, and an ultra-fine grain structure is obtained. According to the rigging steel provided by the invention, equipment, a mold and a preparation process are greatly simplified; the strength and corrosion resistance of the rigging steel are greatly improved. The ultrahigh-strength corrosion-resistant rigging steel provided by the invention can be applied to a plurality of important fields of cables for ships, long-span bridge cables, cables for heavy cranes and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of design, preparation and application of ultra-high strength corrosion-resistant rigging steel materials, and in particular to a 3GPa ultra-high strength corrosion-resistant rigging steel and a preparation method thereof. Background Art

[0002] Rigging steel is widely used in many fields such as ship cables, long-span bridge cables, and heavy crane cables. At present, ship cables usually use cold-drawn pearlite steel wire with a diameter of φ5mm to φ7mm, and its tensile strength is generally between 1770 and 2060MPa. Due to the poor corrosion resistance of cold-drawn pearlite steel wire, in order to avoid rust during service, it is necessary to galvanize its surface, which will undoubtedly significantly increase the preparation cost of rigging steel. People are in urgent need of developing new rigging steel with higher strength and higher corrosion resistance.

[0003] Studies have shown that grain refinement can not only effectively hinder the movement of dislocations and thus improve the strength of the material, but also facilitate uniform corrosion of the material and improve the stability of the passivation film on the surface of the material, thereby improving the corrosion resistance of the material. The preparation of ultrafine-grained metal materials is mainly achieved through the large plastic deformation (SPD) method. Common large plastic deformation methods include equal channel angular pressing (ECAP), cumulative composite rolling (ARB), multidirectional forging (MF) and high pressure torsion (HPT). These methods all require high-power equipment and expensive molds, and the size of the prepared materials is also small, which cannot meet the needs of large-scale industrial production. Therefore, a new type of low-cost and large-scale preparation technology for ultrafine-grained rigging steel is urgently needed.

[0004] In addition, optimizing the chemical composition of the rigging steel and adding Mo and Al elements can improve its strength and corrosion resistance. On the one hand, after severe cold deformation, the dislocation density inside the rigging steel increases sharply, resulting in a decrease in the stability of the material structure. Dislocations and ultrafine grains are prone to recovery or coarsening and growing during cold drawing, causing the rigging steel to soften during continuous drawing. Adding the Mo element can reduce the diffusion coefficient of the matrix and inhibit the climb recovery of dislocations; adding the Al element can prevent the carbides in the rigging steel from aggregating and growing. Therefore, adding Mo and Al can improve the strength of the rigging steel after cold drawing. On the other hand, the Mo element can improve the stability of the passivation film, while the Al element is beneficial to promote the formation of dense Al on the surface of the rigging steel. 2 O 3 Passivation film, so adding Mo and Al elements can also improve the corrosion resistance of steel materials.

[0005] Therefore, people are eager to obtain an ultra-high strength corrosion-resistant rigging steel with better technical effects and a preparation method thereof. Summary of the invention

[0006] The present invention provides an ultrafine-grained 0.8C3Al0.7Mo rigging steel having ultrahigh strength of more than 3 GPa and excellent corrosion resistance and a preparation method thereof, which is expected to promote the optimization and upgrading of existing rigging steel materials.

[0007] The invention discloses a 3GPa ultra-high strength corrosion-resistant rigging steel, the key technology of which is: by weight percentage, the chemical composition and weight percentage of the rigging steel meet the following requirements: C: 0.6-1.0; Al: 2.2-3.8; Mo: 0.3-1.1; the balance is Fe. Further preferred limiting content: by weight percentage, the chemical composition and weight percentage of the rigging steel meet the following requirements: C: 0.75-0.85; Al: 2.8-3.2; Mo: 0.6-0.8; the balance is Fe.

[0008] The present invention also claims to protect the preparation method of the aforementioned 3GPa ultra-high strength corrosion-resistant rigging steel, the technical key of which is: the preparation method of the 3GPa ultra-high strength corrosion-resistant rigging steel meets the following requirements:

[0009] The chemical composition and weight percentage of the raw material meet the following requirements: C: 0.6-1.0; Al: 2.2-3.8; Mo: 0.3-1.1; the balance is Fe;

[0010] The 3GPa ultra-high strength and corrosion-resistant rigging steel is obtained by melting in a vacuum induction furnace and then forging the billet at above 1150°C.

[0011] The preparation method of the 3GPa ultra-high strength corrosion-resistant rigging steel meets the following requirements: the initial structure of the hot-rolled billet is a full martensite structure, and the structure is subjected to multiple hot rolling in the (α+γ) two-phase region at 800-880°C to obtain an ultrafine grain structure.

[0012] The rolling deformation temperature is 830-850°C; the hot rolling deformation degree is not less than 90%.

[0013] The rolled and deformed material is cold drawn, and the cold drawing deformation is not less than 80%.

[0014] The material after cold drawing deformation is annealed at a temperature of 150° C. for 1 hour.

[0015] The microstructure is a banded ultrafine-grained ferrite + martensite structure, with a yield strength of 2150-3050MPa, a tensile strength of 2550-3450MPa, an elongation of 3-10%, and a self-corrosion current of 0.2-1μA / cm in a 3.5% NaCl aqueous solution. 2 .

[0016] In order to develop 3GPa ultra-high strength and corrosion-resistant rigging steel, the present invention adds Al and Mo elements to the traditional T8 carbon steel and designs an ultrafine-grained 0.8C3Al0.7Mo rigging steel. Its ultrafine-grained structure and Mo and Al alloying will be used to improve the strength and corrosion resistance of the rigging steel. In order to achieve the preparation of ultrafine-grained structure, the present invention performs solid solution and quenching on 0.8C3Al0.7Mo steel in the austenite single-phase region to obtain a martensitic structure. Subsequently, the martensitic structure is hot-rolled in the (α+γ) two-phase region, and the strain energy and interface energy stored in the martensitic structure will provide a strong driving force for the dynamic recrystallization of the α phase, thereby greatly improving the dynamic recrystallization nucleation rate. At the same time, during the hot rolling process, the martensite will decompose α′→α+γ, and the decomposition product γ phase can pin the α grains, inhibit the coarsening and growth of the dynamic recrystallization nuclei, and enable the material to obtain an ultrafine-grained structure after deformation. The ultrafine grain structure is then cold drawn. Since Mo and Al can improve the stability of the microstructure, inhibit the recovery of dislocations and the aggregation and growth of carbides, the strength of the ultrafine grains will be further improved. After cold drawing, the plasticity and toughness of the material can be improved through low-temperature tempering, and finally 3GPa ultra-high strength and corrosion-resistant 0.8C3Al0.7Mo rigging steel is prepared.

[0017] Different from the prior art, the rigging steel provided by the present invention can realize the preparation of ultrafine-grained ultra-high-strength rigging steel through conventional thermal deformation without relying on high-power equipment and expensive molds. The present invention greatly improves the strength and corrosion resistance of rigging steel. Its yield strength is 2150-3050MPa, tensile strength is 2550-3450MPa, elongation is 3-10%, and self-corrosion current in 3.5% NaCl aqueous solution is 0.2-1μA / cm 2 The ultra-high strength and corrosion-resistant rigging steel provided by the present invention can be used in many important fields such as ship cables, large-span bridge cables, and heavy crane cables. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Optical microstructure photograph of the rigging steel after hot rolling in Example 5;

[0019] Figure 2 SEM microstructure photograph of the rigging steel after hot rolling in Example 5;

[0020] Figure 3 This is the SEM microstructure photograph of the rigging steel in Comparative Example 10 after cold drawing. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the embodiments and the accompanying drawings, but is not limited thereto.

[0022] In order to make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below with reference to the accompanying drawings and examples.

[0023] The invention provides a novel rigging steel, the chemical composition of which is: C: 0.6-1.0; Al: 2.2-3.8; Mo: 0.3-1.1; the remainder is Fe.

[0024] See also Figure 1 , Figure 1 This is the optical microstructure of the rigging steel of Example 5 of the present invention after hot rolling. It can be seen that the microstructure is uniform and the grain size is extremely small, so that it is difficult to identify the grain morphology through an optical microscope.

[0025] See also Figure 2 , Figure 2 This is the SEM structure of the rigging steel of Example 5 of the present invention after hot rolling. It can be seen that its microstructure is composed of ultrafine-grained ferrite + martensite, and their grain size is 1.2±0.6μm.

[0026] Figure 3 This is a SEM photograph of the rigging after cold drawing in Comparative Example 10. It can be seen that its microstructural morphology is significantly different from the band-shaped ultrafine crystal morphology provided by the present invention.

[0027] The present application will be described and explained below through several groups of specific embodiments and comparative examples, but they should not be used to limit the scope of the present application.

[0028] Embodiment: Embodiments 1 to 9 are 0.8C3Al0.7Mo rigging steels smelted within the chemical composition range provided by the present invention, wherein the contents of C, Al and Mo elements are gradually increased, and the corresponding preparation process is also appropriately adjusted within the technical parameter range specified in the present invention.

[0029] Comparative Examples: The chemical composition of Comparative Example 1 is lower than the lower limit of the chemical composition range provided by the present invention, and the chemical composition of Comparative Example 9 is higher than the upper limit of the chemical composition range provided by the present invention. By comparing with Example 1 and Example 9, respectively, the influence of chemical composition on the structure and performance of rigging steel is explained.

[0030] In Comparative Example 2, the quenching temperature of the forging blank is lower than the temperature specified in the present invention. By comparing with Example 2, the influence of the quenching temperature of the forging blank on the structure and properties of the rigging steel is explained.

[0031] In Comparative Example 3, the cooling method of the forging blank after solution treatment is not quenching as specified in the present invention, but furnace cooling. By comparing with Example 3, the influence of the cooling method of the forging blank after solution treatment on the structure and properties of the rigging steel is explained.

[0032] The rolling deformation temperature of comparative example 4 is higher than the upper limit specified in the present invention, and the rolling deformation temperature of comparative example 5 is lower than the lower limit specified in the present invention. By comparing with examples 4 and 5, the influence of rolling temperature on the structure and performance of rigging steel is explained.

[0033] The hot rolling deformation of Comparative Example 6 is lower than the lower limit of deformation specified in the present invention. By comparing with Example 6, the influence of hot rolling deformation on the structure and performance of rigging steel is explained.

[0034] The cold drawing deformation of Comparative Example 7 is lower than the lower limit specified in the present invention. By comparing with Example 7, the influence of the cold drawing deformation on the structure and performance of the rigging steel is explained.

[0035] Comparative Example 9 was not annealed after cold drawing. By comparing it with Example 8, the effect of the annealing process after cold drawing on the material properties is explained.

[0036] Comparative Example 10 is a commercial T8 rigging steel, and by comparing it with Examples 1 to 9 of the present invention, the organizational and performance advantages of the rigging steel provided by the present invention are illustrated.

[0037] Microstructure characterization: Zeiss optical microscope and TESCAN scanning electron microscope (SEM) were used to characterize the microstructure of the material. After mechanical grinding and polishing, the test sample was etched with Velocity etching solution for 20 seconds to observe its microstructure morphology. The experimental results are shown in Figure 1 , 2, 5. The microstructure of the material was characterized by a Talos F200x transmission electron microscope (TEM). After the sample was manually thinned to 50 nm, it was chemically double-sprayed in a 10 vol. % HClO4 + 90 vol. % C2H5OH solution. The voltage during thinning was set to 25 V and the temperature was -25 ° C. The experimental results are shown in Figure 3 shown.

[0038] Mechanical properties test: Processed according to GBT228.1-2010 standard Standard cylindrical tensile specimen. Subsequently, the room temperature tensile properties of the material were tested using an Instron 8872 tensile testing machine. The crossbeam displacement rate of the tensile test was 0.5 mm / min, and the average value of three measurements was taken as the tensile properties of the material. The tensile strength, yield strength and elongation are shown in Table 2.

[0039] Electrochemical test: The electrochemical experiment instrument uses a Gamry electrochemical workstation (Gamry Reference600, USA), the experimental temperature is 23°C, the electrolyte is 3.5% NaCl solution, the electrolytic cell is a standard three-electrode system, the sample is the working electrode, the metal platinum sheet is the auxiliary electrode, and the saturated KCl calomel electrode is the reference electrode. Before the potentiodynamic polarization curve test, a 1h open circuit potential test is performed to stabilize the electrode potential. During the polarization curve test, the scanning rate is 0.5mV / s. The electrochemical experimental data are analyzed using Gamry Echem Analyst software. Three parallel samples are prepared for each group of samples, and the self-corrosion current I corr The value is the average of 3 measurements. The experimental results are shown in Table 2 and Figure 3 shown.

[0040] Table 1 Chemical composition and preparation process of materials in Examples and Comparative Examples

[0041]

[0042] The preparation process of Examples 1-9 and Comparative Examples 1-10 is described as follows:

[0043] Example 1: The ingot was forged at 1150°C, then kept at 1150°C for 1 hour and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 800°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0044] Example 2: The ingot was forged at 1150°C, then kept at 1150°C for 1 hour and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 810°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0045] Example 3: The ingot was forged at 1150°C, then kept at 1150°C for 2 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 820°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0046] Example 4: The ingot was forged at 1150°C, then kept at 1150°C for 2 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 830°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0047] Example 5: The ingot was forged at 1150°C, then kept at 1150°C for 2 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 840°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0048] Example 6: The ingot was forged at 1150°C, then kept at 1150°C for 3 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 850°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0049] Example 7: The ingot was forged at 1150°C, then kept at 1150°C for 3 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 860°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0050] Example 8: The ingot was forged at 1150°C, then kept at 1150°C for 3 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 870°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0051] Example 9: The ingot was forged at 1150°C, then kept at 1150°C for 3 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 880°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0052] Comparative Example 1: The ingot was forged at 1150°C, then kept at 1150°C for 1 hour and then oil quenched to room temperature. The quenched ingot was hot rolled at 800°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0053] Comparative Example 2: The ingot was forged at 1150°C, then kept at 750°C for 1 hour and oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 810°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0054] Comparative Example 3: The ingot was forged at 1150°C, then kept at 1150°C for 2 hours and then slowly cooled to room temperature in the furnace. The furnace-cooled ingot was hot-rolled at 820°C, with a rolling deformation greater than 90%. It was then cold-drawn, with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour.

[0055] Comparative Example 4: The ingot was forged at 1150°C, then kept at 1150°C for 2 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 1150°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0056] Comparative Example 5: The ingot was forged at 1150°C, then kept at 1150°C for 2 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 600°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0057] Comparative Example 6: The ingot was forged at 1150°C, then kept at 1150°C for 3 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 850°C with a rolling deformation of 30%. It was then cold drawn with a drawing deformation of not less than 80%, and annealed at 150°C for 1 hour after cold drawing.

[0058] Comparative Example 7: The ingot was forged at 1150°C, then kept at 1150°C for 3 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 860°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of 25%, and annealed at 150°C for 1 hour after cold drawing.

[0059] Comparative Example 8: The ingot was forged at 1150°C, then kept at 1150°C for 3 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 870°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of 20%, and annealed at 150°C for 1 hour after cold drawing.

[0060] Comparative Example 9: The ingot was forged at 1150°C, then kept at 1150°C for 3 hours and then oil quenched to room temperature to obtain a martensitic billet. The martensitic billet was hot rolled at 880°C with a rolling deformation greater than 90%. It was then cold drawn with a drawing deformation of not less than 80%.

[0061] Comparative Example 10: The ingot is forged at 1200° C., and then the forged billet is hot rolled at a rolling temperature of 900° C. with a rolling deformation greater than 90%. Finally, the hot rolled bar is cold drawn with a cold drawing deformation greater than 80%.

[0062] Table 2 Organization characteristics and properties of materials in Examples and Comparative Examples

[0063]

[0064]

[0065] From the results in Table 2, it can be seen that Examples 1 to 9 are all banded ultrafine-grained ferrite + martensite structures, and they all have high strength. As the content of C, Al, and Mo elements increases, the yield strength σ s , tensile strength σ b The elongation δ and self-corrosion current density I corr Gradually decrease.

[0066] The C, Al and Mo contents of Comparative Example 1 are all lower than the lower limits specified in the present invention, which results in coarse grains, and the yield strength and tensile strength of the material are significantly lower than those of Example 1 of the present invention. corr It is significantly higher than Example 1 of the present invention, indicating that its corrosion resistance is also lower than Example 1 of the present invention. The C, Al, and Mo contents of Comparative Example 9 are all higher than the upper limits specified in the present invention. Although its strength and corrosion resistance are higher than those of Example 9 of the present invention, the elongation of the material is much lower than that of Example 9 of the present invention.

[0067] The quenching temperature of the forging blank in Comparative Example 2 is lower than the temperature specified in the present invention, and its structure is a cold-drawn pearlite structure, rather than a banded ultrafine-grained ferrite + martensite structure in Example 2 of the present invention. Its yield strength and tensile strength are significantly lower than those in Example 2 of the present invention. corr It is obviously higher than Example 2 of the present invention, so the corrosion resistance is not as good as that of the example of the present invention.

[0068] The cooling method of the forging blank in Comparative Example 3 after solution treatment is not quenching as specified in the present invention, but furnace cooling, which results in a coarse grain size of the prepared material. Therefore, its yield strength, tensile strength and corrosion resistance are significantly lower than those of Example 3 of the present invention.

[0069] The rolling deformation temperature of comparative example 4 is higher than the upper limit specified in the present invention. After rolling deformation, it obtains cold-drawn pearlite structure, and its yield strength, tensile strength and corrosion resistance are significantly lower than those of example 4 of the present invention.

[0070] The rolling deformation temperature of comparative example 5 is lower than the lower limit specified in the present invention. After rolling deformation, it obtains a banded ultrafine-grained ferrite structure, and its yield strength, tensile strength, elongation and corrosion resistance are significantly lower than those of Example 5 of the present invention.

[0071] The hot rolling deformation of Comparative Example 6 is lower than the lower limit of hot rolling deformation specified in the present invention, and its ferrite width is significantly higher than that of Example 6 of the present invention, and its yield strength, tensile strength and corrosion resistance are also significantly lower than those of Example 6 of the present invention.

[0072] The cold rolling deformation of comparative example 7 is lower than the lower limit of cold rolling deformation specified in the present invention, and its ferrite width is significantly higher than that of example 7 of the present invention, and its yield strength, tensile strength and corrosion resistance are also significantly lower than those of example 6 of the present invention.

[0073] The material of Comparative Example 8 was not annealed after cold rolling. Although its strength was slightly higher than that of Example 8 of the present invention, its plasticity and corrosion resistance were significantly lower than those of Example 8 of the present invention.

[0074] Comparative Example 10 shows the structure and properties of commercial T8 rigging steel after cold drawing. Its microstructure is a cold-drawn pearlite structure, rather than the banded ultrafine-grained ferrite + martensite structure provided by the present invention. By comparing with Examples 1 to 9 of the present invention, it can be seen that the strength, plasticity and corrosion resistance of the material provided by the present invention are significantly better than those of commercial T8 rigging steel.

[0075] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. 3GPa ultra-high strength corrosion-resistant rigging steel, characterized by: The chemical composition and weight percentage of the rigging steel meet the following requirements: C: 0.6~1.0; Al: 2.2~3.8; Mo: 0.3~1.1; the balance is Fe.

2. The 3GPa ultra-high strength corrosion-resistant rigging steel according to claim 1, characterized in that: The chemical composition and weight percentage of the rigging steel meet the following requirements: C: 0.75~0.85; Al: 2.8~3.2; Mo: 0.6~0.8; the balance is Fe.

3. The method for preparing the 3GPa ultra-high strength corrosion-resistant rigging steel according to claim 1, characterized in that: The preparation method of the 3GPa ultra-high strength and corrosion-resistant rigging steel meets the following requirements: smelting is carried out in a vacuum induction furnace, and then the billet is forged at above 1150°C to obtain the 3GPa ultra-high strength and corrosion-resistant rigging steel.

4. The method for preparing the 3GPa ultra-high strength corrosion-resistant rigging steel according to claim 3, characterized in that: The preparation method of the 3GPa ultra-high strength corrosion-resistant rigging steel meets the following requirements: The chemical composition and weight percentage of the raw material meet the following requirements: C: 0.6-1.0; Al: 2.2-3.8; Mo: 0.3-1.1; the balance is Fe; The initial structure of the hot-rolled billet is a full martensite structure, which is subjected to multiple hot rolling in the (α+γ) two-phase region at 800-880°C to obtain an ultrafine grain structure.

5. The method for preparing the 3GPa ultra-high strength corrosion-resistant rigging steel according to claim 3 or 4, characterized in that: The preparation method of the 3GPa ultra-high strength corrosion-resistant rigging steel meets the following requirements: The rolling deformation temperature is 830-850°C; the hot rolling deformation degree is not less than 90%.

6. The method for preparing the 3GPa ultra-high strength corrosion-resistant rigging steel according to claim 5, characterized in that: The preparation method of the 3GPa ultra-high strength corrosion-resistant rigging steel meets the following requirements: The rolled and deformed material is cold drawn, and the cold drawing deformation is not less than 80%.

7. The method for preparing the 3GPa ultra-high strength corrosion-resistant rigging steel according to claim 6, characterized in that: The preparation method of the 3GPa ultra-high strength corrosion-resistant rigging steel meets the following requirements: the material after cold drawing deformation is annealed at a temperature of 150° C. and an annealing time of 1 hour.

Citation Information

Patent Citations

  • Intrinsic non-net secondary cementite steel and application method thereof

    CN101619412A

  • Preparation method of powder metallurgical gear and chain wheel

    CN105014077A

  • Improvement in method for prepn. of high-strength fine wire of high-carbon steel

    CN1072460A

  • graphitic special steels and nitrided products based on these steels

    FR910513A

  • Weld metal joint having excellent low temperature toughness

    KR1020130003685A

Cited By

  • 3000mpa grade ultra-high strength steel wire and method for manufacturing the same

    CN122686915A